QOLP-13. COMPARISON OF SYMPTOM BURDEN AND ASSOCIATED IMPACT ON DAILY LIFE IN GLIOBLASTOMA PATIENTS TREATED WITH AND WITHOUT TUMOR TREATING FIELDS. (9th November 2020) - Tipps, Megan; Tierney, Meghan; Monson, Caitlin; Jackson, Kelsey; Banerji, Nilanjana; Bruns, Patricia; Trusheim, John
Abstract: INTRODUCTION: Clinical trials have demonstrated that the use of low intensity alternating electric fields, known as Tumor Treating Fields (TTFields), via the Optune™ device extends overall survival times in patients with glioblastoma when combined with standard chemotherapy. In addition to survival time, quality of life (QOL) is an important factor in treatment decisions for life-limiting diagnoses. Examinations of the impact of TTFields on QOL have yielded mixed RESULTS: Here, we describe patient-reported symptoms in patients with glioblastoma undergoing treatment with TTFields and compare symptom burden and associated interference with daily life to that of a historic non-TTFields cohort. METHODS: Patients with primary glioblastoma who chose treatment with the Optune™ device were prospectively enrolled and asked to complete the brain tumor-specific MD Anderson Symptom Inventory (MDASI-BT) approximately every 8 weeks through cessation of active disease treatment. MDASI-BT assessments were examined for symptom frequency, severity, and relationships between symptom severity and interference with daily life. These results were also compared with a matched cohort of patients who did not chose TTFields treatment and completed MDASI-BT assessments as part of a previous study. RESULTS: The most commonly reported symptoms for Optune™ users were fatigue, sleep disturbance and speaking/word finding. Fatigue and sleep disturbance were also among the symptoms rated as most severe, along with feeling drowsy/sleepy. Interference with general activities and overall enjoyment of life as both were reported as both the most common and most severe impacts on daily life. When compared with historic data from non-Optune™ users at the same point in treatment, we found no difference in either symptom burden (p=0.48) or interference scores (p=0.72). CONCLUSION: Attention to both survival benefit and symptom experience related to treatment options can inform patient decisions and direct approaches to symptom management as well as improved QOL.